2021
DOI: 10.3390/coatings11080954
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Film-Forming Properties of Millet Starches: A Comparative Study

Abstract: Millets are an underutilized and important drought-resistant crop, which are mainly used for animal feed. The major constituent in millet is starch (70%); millet starch represents an alternative source of starches like maize, rice, potato, etc. This encouraged us to isolate and characterize the starches from different millet sources and to evaluate the application of these starches in edible film preparation. In the present study, the physicochemical, morphological, and film-forming characteristics of millet s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Additionally, starch-based packing materials (films) are safe, easy to prepare, environmentally friendly, and convenient to use [8][9][10]. The utilization of starch and its properties also helps to explore different botanical resources [11].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, starch-based packing materials (films) are safe, easy to prepare, environmentally friendly, and convenient to use [8][9][10]. The utilization of starch and its properties also helps to explore different botanical resources [11].…”
Section: Introductionmentioning
confidence: 99%
“…Its value decreased as the concentration of EPI increased to modify the starch. Bangar et al [43] observed TS value for millet starches from 3.79 to 6.95 MPa, and the EAB values at 53.4% to 73.2%, respectively. Bruni et al [44] observed an increase in the TS value for films prepared from CL wheat starch in comparison to native starch.…”
Section: Properties Of Starch Filmsmentioning
confidence: 97%
“…The stable OW emulsion obtained was then dropped (dropping method) into a stirred 2% (w/v) solution of CaCl 2 at a concentration of 1 mM in water (as a hardening water bath), using a peristaltic pump with an injector measuring 0.4 mm × 20 mm, and was then stirred for ~1 h [25,39]. After 1 h of curing, the hydrogel beads obtained using ionotropic gelation and the cross linking technique were separated from the hardening bath, washed with deionized water, then they were put on Petri dishes covered with filter paper to remove the remaining water.…”
Section: Preparation Of Hydrogel Beadsmentioning
confidence: 99%
“…The encapsulation of oils using various techniques has become increasingly popular as a promising preservation method [23]. Therefore, studies have been carried out to optimize process factors for the encapsulation of oils with maximum efficiency [24,25].…”
Section: Introductionmentioning
confidence: 99%